Total L1 vertebrectomy with T12-to-L2 fusion in a case of burst fracture - Ozveren, MF; Erol, FS; Kaplan, M; Yakar, H (Lippincott Williams & Wilkins, 2005)
Objective: To present a novel technique aiming at fusion of the upper and lower vertebrae by removal of the anterior and posterior elements of a lumbar vertebra. Methods: A 26-year-old male patient presented with a posttraumatic L1 vertebra fracture and total paraplegia. Three weeks after corpectomy plus otogenic bone grafting plus instrumentation by an anterolateral approach, the patient, who had 3-column injury, developed a treatment-resistant deep wound infection. In the fourth week of antibiotic treatment after the onset of the infection, there was no improvement, and the vertebral stabilization provided by the instrumentation was disrupted. Thus, the fixators and autograft were removed, the L1 posterior elements were totally excised, and compressive posterior instrumentation was performed. Results: Fusion stabilization was achieved in the patient with treatment-resistant postoperative deep wound infection after anterior instrumentation through a total vertebrectomy plus a posterior instrumentation technique.
Keywords: instrumentation; postoperative deep wound infection; spinal trauma; vertebrectomy